Antibiotic susceptibility pattern of resistant Escherichia Coli from poultry waste - Shrestha, S (BIBECHANA, 2012)
The study was conducted in Kathmandu valley to investigate the relationship between the use of antibiotic and the development of the resistant form of Escherichia coli (E.coli), which were isolated from faecal waste of poultry farm. Out of 30 samples investigated, 20 samples were found to be E.coli positive. It was further investigated that the resistance pattern for the isolates of E.coli from poultry farm was tetracycline (100%), penicillin (100%), erythromycin (100%), amoxicillin (90%) and chloramphenicol (60%). DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7188 BIBECHANA 9 (2013) 136-140